The development of activated carbon from biomass precursors - Gill, Andrew (2017)
The focus of this paper is to investigate the production of activated carbon from biomass on laboratory (lab) and pilot scales. Different biomass sources (> 30) were pyrolysed and steam activated on a lab scale to assess final quality. These were reduced to six based on potential, which were then activated under different temperatures and residence times to develop an analysis matrix. From this and other set criteria, olive stone and pine wood - a granular and powder carbon respectively - were chosen. The biomass chars were tested and compared under many production variables in lab and pilot scale production. Further novel findings: Linear burn off rates were seen by increasing activation temperature residence time, and an exponential burn off by increasing water flow. In both lab and pilot scale there was direct linear correlation between burn off percentage and CTC (carbon tetrachloride activity) values for both biomasses proving scalability, this was maintained as porosity changed with increasing burn off. The maximum CTC value for olive stone was found to be 84.5 at 74% burn off using activation conditions of 775 oC, 120 minutes and 1.125 ml/min water flow rate. Pine wood produced a peak CTC value of 120 at 80% to 82% burn off using activations conditions of 800 oC, 90 minutes and 1.5 ml/min water flow rate. Both carbons produced a higher CTC than a tested commercial carbon (60). The CTC values curtailed after > 80% and > 85% burn off for olive stone and pine wood respectively due to destruction and high ash to carbon ratios. Methylene blue numbers were seen up to 22 (330 mg/g) and 25 (375 mg/g) for olive stone and pine wood respectively. Olive stone produced surface areas up to (1157 m2/g) micropore volumes (0.458 cm3/g), mesopore volumes (0.317 cm3/g) and total pore volumes up to (0.753 cm3/g) with this surface area, mesopore volume and total pore volumes were the highest found in literature for steam activation. Pine wood produced surface areas up to (1190 m2/g), micropore volumes (0.472 cm3/g), mesopore volumes (0.589 cm3/g) and total pore volume to (1.061 cm3/g), all higher than any current reported values using steam activation. Production variable limits prior to excessive burn off were found for both biomasses: Activation temperatures over 850 oC and 825 oC for olive stone and pine wood respectively, olive stone with a residence time of > 6 hours and steam flow rate of > 1.875 ml/min whereas there proved to be no adverse effects to long residence times and high steam flow rates with pine wood. This was deduced to be due to a higher mass transfer limitation seen with the higher density olive stone resulting in external particle ablation. Single step production was carried out on lab and pilot scale with no negative effects seen to adsorption properties and pore structures. The produced carbons was comparable to the products produced by the usual two-step process. Calcium oxide ash component in pine wood is lost during production proved by ion chromatography analysis. Hot water washing biomass had no effect on the burn off percentage, CTC correlation only on the individual burn off percentage and total yields of the carbons. An OPEX/CAPEX cost analysis was completed and showed that both carbons are potentially profitable products.